Experimental Investigation Of Castor Oil As An Alternative Fuel For Biodiesel - Abu Saleh, Ahmed; Ismail, S.; Rahman, R.; Sinin, Hamdan (2014)
In this study, the efficiency of biodiesel conversion from crude castor oil to castor biodiesel (CB) through transesterification method was investigated. The acid-base catalyzed transesterification under different reaction condition such as the molar ratio of alcohol and mass ratio of catalyst to oil was studied for optimum proportion to achieve highest yield of Castor biodiesel. The optimum condition for acid-base catalyzed transesterification was determined to be 0.22 oil/methanol (v/v) and 0.005 KOH/oil (v/v). The potential of CaCO3 to be used as solid base catalyst for transesterification of castor oil was also investigated. Then the fuel properties of the produced castor biodiesel such as the calorific value, flash point and density were analyzed. Component analysis was carried out by using FT-IR. The diesel engine performance and emission test using different castor biodiesel blends were then conducted. B20 blend of castor biodiesel was proved to have the same engine power output as mineral diesel with lower average percentage of change in CO, PM and HC emissions compared to mineral diesel. Thus a B20 blend of castor biodiesel was a suitable alternative fuel for diesel.